A P2P-based incremental web ranking algorithm - Sangamuang S. (2014)
In this paper, we propose an incremental algorithm for web ranking in the Peer-to-Peer (P2P) environments. Not the same as the non-incremental algorithm, the proposed algorithm can partition the web link graphs, the graphs represented the connectivity structure among the web pages, into the changed sub graphs, and the unchanged sub graphs. Subsequently, the algorithm processes only the necessary data in order to compute the ranking. The experiments have been conducted to evaluate the efficiency of the algorithm, comparing with the non-incremental algorithm in various P2P environments. We report the efficiency in terms of both computational and communication costs. It has been found that in terms of communication cost, the proposed algorithm can out perform the traditional one in all configurations. For the computational cost, the proposed algorithm can out perform the traditional one in all P2P network sizes but it has slightly higher computational cost when the web link graph size is large. © 2011 IEEE.